In silico Computational Analysis of Siddha Formulation Veppampoo mathirai in Inhibition of Angiotensin-Converting Enzyme Receptor Target against Hypertension (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Hypertension (HTN) is a leading non-communicable disease in the world which affects mostpeople. Even though, modern medicines are available widely, people show their interest to take traditionalsystem of medicines like Siddha to overcome some untoward side effects. In this regard, Veppampoomathirai, apolyherbal siddha formulation prescribed for HTN was studied by in silico computational analysis for its potentialaction against HTN in inhibition of Angiotensin-converting enzyme receptor target compared with standardcaptopril drug of modern medicine. Materials and Methods: The phytochemicals present in the formulationwere identified, selected, and retrieved through literature survey. Molecular docking analysis was performedby AutoDock tool version 4. The lead molecules were identified by their binding affinity toward target enzymeangiotensin-converting enzyme (ACE) and compared with standard captopril. Results: The phytoprinciples suchas Ascorbic acid, Elemene, Cinnamaldehyde, Gallic Acid, Nimbiol, Piperic acid, Piperine, Eugenol, Nimbolide,Rutin, and Solasodine had 7–10 interactions with more interaction surface area. Nimbiol and Gallic acid hadten interactions, whereas Piperic acid, Peperine, and Nimbolide had nine interactions which are higher than thestandard Captopril with the active amino acids at the target ACE enzyme. Conclusion: The study concludesthat the formulation Veppampoomathirai has potential binding action against ACE target enzyme that helps inreducing blood pressure.